2016
DOI: 10.1016/j.ejphar.2016.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acetyl-CoA carboxylases by soraphen A prevents lipid accumulation and adipocyte differentiation in 3T3-L1 cells

Abstract: Acetyl-CoA carboxylases (ACC) 1 and 2 catalyze the carboxylation of acetyl-CoA to malonyl-CoA and depend on biotin as a coenzyme. ACC1 localizes in the cytoplasm and produces malonyl-CoA for fatty acid (FA) synthesis. ACC2 localizes in the outer mitochondrial membrane and produces malonyl-CoA that inhibits FA import into mitochondria for subsequent oxidation. We hypothesized that ACCs are checkpoints in adipocyte differentiation and tested this hypothesis using the ACC1 and ACC2 inhibitor soraphen A (SA) in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Adiponectin acts as one of adipokines that can enhance adipocyte differentiation and lipid accumulation in mature adipocytes [ 31 ]. Acetyl-CoA carboxylase (ACC)-1 catalyzes fatty acid synthesis and contributes to lipid accumulation and adipogenesis in adipocytes [ 32 ]. Fatty acid synthase (FAS) is predominantly expressed in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin acts as one of adipokines that can enhance adipocyte differentiation and lipid accumulation in mature adipocytes [ 31 ]. Acetyl-CoA carboxylase (ACC)-1 catalyzes fatty acid synthesis and contributes to lipid accumulation and adipogenesis in adipocytes [ 32 ]. Fatty acid synthase (FAS) is predominantly expressed in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence that in our tumoral tissue only the mutated transcript is present, we can assume that, even if protein level is decreased, the isoform loses negative control by BRCA1 and remains active. In this case, patient could potentially benefit from a therapy with ACACA inhibitors such as miR-195 [ 28 ] or soraphen A [ 29 ] ( Fig. 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have demonstrated that several adipogenic transcription factors, including the family of CCAAT/enhancer-binding proteins (C/EBPs), peroxisome proliferator-activated receptors (PPARs), and signal transducer and activator of transcription (STAT) proteins play a pivotal role in preadipocyte differentiation by regulating the expression of genes related to this process [ 9 , 10 ]. It also has been shown that fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), and perilipin A, which regulate lipogenesis and LDs maturation/stabilization are crucial for preadipocyte differentiation [ 11 , 12 , 13 ]. Moreover, there is evidence pointing out the positive role of numerous signaling protein kinases, such as cAMP-activated protein kinase (AMPK), protein kinase A (PKA), extracellular signal-regulated protein kinase-1/2 (ERK-1/2), p38 mitogen-activated protein kinase (MAPK), and protein kinase C (PKC) in preadipocyte differentiation [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%